Protocol for a hybrid effectiveness-implementation clinical trial evaluating video-assisted electronic consent vs standard consent for patients initiating and continuing haemodialysis in Australia (eConsent HD) - Helen Healy; Ann Bonner; Rebecca B Saunderson; Martin Wolley; Chenlei Kelly Li; Pedro Henrique Franca Gois; Marina Wainstein; Matthew J Damasiewicz; Vera Y Miao; Kirsten Hepburn; Clyson Mutatiri; Bobby Chacko (BMJ Open)
Introduction Communicating complex information about haemodialysis (HD) and ensuring it is well understood remains a challenge for clinicians. Informed consent is a high-impact checkpoint in augmenting patients’ decision awareness and engagement prior to HD. The aims of this study are to (1) develop a digital information interface to better equip patients in the decision-making process to undergo HD; (2) evaluate the effectiveness of the co-designed digital information interface to improve patient outcomes; and (3) evaluate an implementation strategy.Methods and analysis First, a co-design process involving consumers and clinicians to develop audio-visual content for an innovative digital platform. Next a two-armed, open-label, multicentre, randomised controlled trial will compare the digital interface to the current informed consent practice among adult HD patients (n=244). Participants will be randomly assigned to either the intervention or control group. Intervention group: Participants will be coached to an online platform that delivers a simple-to-understand animation and knowledge test questions prior to signing an electronic consent form. Control group: Participants will be consented conventionally by a clinician and sign a paper consent form. Primary outcome is decision regret, with secondary outcomes including patient-reported experience, comprehension, anxiety, satisfaction, adherence to renal care, dialysis withdrawal, consent time and qualitative feedback. Implementation of eConsent for HD will be evaluated concurrently using the Consolidation Framework for Implementation Research (CFIR) methodology. Analysis: For the randomised controlled trial, data will be analysed using intention-to-treat statistical methods. Descriptive statistics and CFIR-based analyses will inform implementation evaluation.Ethics and dissemination Human Research Ethics approval has been secured (Metro North Health Human Research Ethics Committee B, HREC/2022/MNHB/86890), and Dissemination will occur through partnerships with stakeholder and consumer groups, scientific meetings, publications and social media releases.Trial registration number Australian and New Zealand Clinical Trials Registry (ACTRN12622001354774).